RANCANG BANGUN APLIKASI GAME EDUKASI TEBAK GAMBAR MAKANAN KHAS INDONESIA BERBASIS ANDROID - Pratiwi, Ersa; M.Kom, Dian Ade Kurnia; M.Kom, Ade Irma Purnamasari (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Nowadays, gadgets are an inseparable part of everyday life, including for children. Today's children are very reliable in using gadgets, and spend a lot of time playing applications (games). Games can be a medium to help hone children's abilities in children's growth and development. Educational games are something that needs to be developed to provide games and get the right information and insight for children. Educational game designed in the form of a game with the concept of matching images of typical Indonesian food with their names and using construct 2 technology. The application design method used is a data collection technique method that uses observation and documentation, the design stages are concept, design, material collection, manufacturing, testing, and distribution. The test was conducted on children respondents with an age range of 11-13 years to obtain data on the level of target satisfaction. The results of the satisfaction level test carried out found that the most appropriate target users were children aged 11-13 years. In general, this game is well received and liked by children and the results of the usability testing application are fairly good and suitable for use by children.